Representations of Epistemological Colonization - Teri Szűcs (International Journal of Roma Studies, 2022)
It can be argued that apart from critically applying the theoretical framework of Postcolonial Studies to Romani Studies, we can effectively describe the position and the history of the European Roma by applying some of the insights of Indigenous Studies. Dipesh Chakrabarty’s conception of “heterotemporality” may play an important role in the dialogue between postcolonial and indigenous theories, addressing temporal plurality of coexistent cultures. In my paper I argue that the hierarchy of powerful and weak narratives is always inscribed into the heterogeneity of historiographies – that is, the plurality of heterotemporal narratives is always inherently hierarchical, being a political construction. I am discussing Béla Osztojkán’s There is Nobody to Pay Jóska Átyin, the magnificent Hungarian Romani historical novel published in 1997, to trace the representations of epistemological oppression, to explore how the colonized, the Romani subaltern is taking part in the discourse of heterotemporality, and finally to see how the fragmented – “different” – historical knowledge is created and articulated in a literary work.